The SAGE Handbook of Qualitative Business and Management Research Methods: History and Traditions - Cassell, Catherine; Cunliffe, Ann L.; Grandy, Gina (London : SAGE Publications Ltd, 2018)
The SAGE Handbook of Qualitative Business and Management Research Methods provides a state-of - the art overview of qualitative research methods in the business and management field. Bringing together a team of leading international researchers, the chapters offer a comprehensive overview of the history and traditions that underpin qualitative research in the field. The chapters in this volume have been arranged into four thematic parts: Part One: Influential Traditions underpinning qualitative research: positivism, interpretivism, pragmatism, constructionism, critical, poststructuralism, hermeneutics, postcolonialism, critical realism, mixed methods, grounded theory, feminist and indigenous approaches. Part Two: Research Designs: ethnography, field research, action research, case studies, process and practice methodologies. Part Three: The Researcher: positionality, reflexivity, ethics, gender and intersectionality, writing from the body, and achieving critical distance. Part Four: Challenges: research design, access and departure, choosing participants, research across boundaries, writing for different audiences, ethics in international research, digital ethics, and publishing qualitative research.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Management -- Research -- Methodology; Qualitative research; Business -- Research; Business -- Research -- Methodology